IOT SECURITY ISSUES: A CASE STUDY ON VULNERABILITIES IN SURVEILLANCE SMART CAMERAS - ABDALLA, PESHRAW AHMED (Fırat Üniveristesi, 2020)
İnternete bağlı cihazların miktarları hızla artıyor. Bu makinelerin çoğuna IoT makineleri denir. IoT cihazları İnternet üzerinden rahatlıkla ilişkilendirilebilir ve kullanılabilir. Bununla birlikte, bu cihazların önemli bir kısmı, bilgisayar korsanları için belirgin kurbanlar olmalarını sağlayan güvenlik açıkları ve kusurları ile üretilmektedir. Bu son zamanlarda medyada yoğun bir şekilde tartışıldı. IP kameralar gibi gözetim cihazları, genellikle uzaktan erişim özelliği ile internet üzerinden bilgi iletebilen, ev, sanayi, yaşlı ve bebek izleme gibi çeşitli ortamlarda ve amaçlar için kullanılan dijital video kameralardır. Canlı video akışı, akıllı telefon, tablet, bilgisayar veya diğer elde taşınır cihazlar gibi çeşitli cihazlardan görülebilir. IP kameralar genellikle hem bant genişliği hem de bilgi işlem açısından güçlüdür ve korsanlar birden fazla saldırı için bu cihazlardan yararlanabildikleri için kendilerine özellikle çekici hale gelir. Bu tezin amacı, IP kameraların güvenlik açıklarını araştırmak ve Kali Linux sızma testi platformunu ve araçlarını kullanarak kullanıcıların güvenliği ve gizliliği üzerindeki etkilerini açıklamaktır. Bu amaçla, tez üç farklı IP kamera üzerinde uygulamalı bir test yapar ve bu kameraların güvenlik bileşenlerini analiz eder. Bu çalışmanın sonuçları, IP kameraların zayıflıkları ve güvenlik eksiklikleri olduğunu ve bu kusurların kullanıcılar üzerinde çeşitli güvenlik etkileri olduğunu göstermektedir. IP kameralarının güvenlik kusurlarından biri fabrika çıkışlı ayarlanmış kullanıcı adları ve şifrelerinin kullanıcılar tarafından değiştirilmemesidir. Aygıtlara yetkisiz erişime çalışan saldırganların (örneğin, Mirai kötü amaçlı yazılımları) önlenmesi için, son kullanıcının varsayılan kimlik bilgilerini değiştirmesi gerekir. Şifrelerin ayarlanması için zayıf şifre politikası, hassas bilgilerin zayıf yöntemlerle şifrelenmesi veya herhangi bir şifreleme olmadan veri gönderilmesi gibi güvenlik açıklarının etkileri ve etkileri, güvenlik çözümleri ve IoT cihazlarının güvenliğini iyileştirmek için öneriler ile birlikte ayrıntılı olarak tartışılmaktadır.

The number of internet-connected devices is growing at a fast rate. A large number of these machines are called the internet of things (IoT) machines. IoT devices can be conveniently associated and used via the internet. However, a considerable number of these devices are made with security vulnerabilities and defects that result in them being obvious targets for hackers. This issue has been extensively discussed in the media recently. An internet protocol (IP) camera is a type of digital video camera that can transmit information over the internet. These cameras are used for several purposes, such as home and industry monitoring, as well as monitoring for babies and the elderly. Also, with the remote access feature of these cameras, a live video stream can be viewed through a number of devices, including smart-phones, tablets, computers, or any other handheld device. IP cameras are usually strong, both in transmission bandwidth and computing, rendering them particularly appealing to hackers, who can exploit these devices with multiple attacks. Distributed Denial-of-Service is one of the attacks that IoT devices, such as IP cameras, are faced with. The purpose of this thesis is to investigate the vulnerabilities of IP cameras and the impact of these vulnerabilities on the security and privacy of IP camera users. This task will be carried out using a Kali Linux penetration testing platform and its tools. To this end, a hands-on test was be performed on three different brands of IP camera (an Intelligent Onvif YY HD camera, a Panoramic IP camera, and a Dual-HD camera), as well as analyzing the security components of these cameras. The outcomes of this study indicate that IP cameras have weaknesses and security problems, that such flaws have various security effects on users. One security flaw of IP cameras is their default usernames and passwords. To prevent attackers that try to access these devices without permission (for instance, using Mirai malware), the end-user must modify the default credentials. The implications and effects of security gaps such as a weak password policy for setting passwords, encryption of sensitive information with weak methods, and sending data without any type of encryption, are discussed in detail. This thesis will also discuss solutions and recommendations to improve the security of IoT devices, especially that of IP cameras.
IoT güvenlik sorunları: Akıllı kameralarda sistem açıkları üzerine deneysel bir çalışma
Keywords: Mühendislik Bilimleri